2015
DOI: 10.1002/ana.24379
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical correlation of urinary retention in lateral medullary infarction

Abstract: We prospectively recruited 10 patients who presented with urinary retention as a neurological deficit that was attributable to lateral medullary infarction. Of these, 9 patients underwent a urodynamic study, which demonstrated detrusor underactivity of the bladder in 7 patients. Urinary retention developed mainly when the lesions involved the lateral tegmentum of the middle or caudal medulla. We concluded that interruption of the descending pathway from the pontine micturition center to the sacral spinal cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
5
12
1
Order By: Relevance
“…Although the neuroimaging study disclosed no abnormality in the brainstem, the blink reflex was abnormal, suggesting a brainstem dysfunction. Moreover, the clinical feature of sphincter disturbance observed in this case was similar to that of patients with lateral medullary infarction reported by Cho et al …”
Section: Discussionsupporting
confidence: 90%
“…Although the neuroimaging study disclosed no abnormality in the brainstem, the blink reflex was abnormal, suggesting a brainstem dysfunction. Moreover, the clinical feature of sphincter disturbance observed in this case was similar to that of patients with lateral medullary infarction reported by Cho et al …”
Section: Discussionsupporting
confidence: 90%
“…Other investigated stroke areas (thalamus, cerebellum, and pons) have been shown to be activated during the micturition phase in PET and fMRI studies [2,3,6,7], and there have been some reported cases of strokes in these areas causing urinary retention [12,13]. Descending pathways of the PMC, including the medulla, have also been associated with voiding function [14], but in our study these areas were not associated with urinary retention. The role of these areas is probably minor in the vast network of urinary control, and damage to these regions may be a risk factor for urinary retention, which may result when patients with strokes in these areas have prostatic hyperatrophy or infections that are further risk factors.…”
Section: Discussioncontrasting
confidence: 50%
“…The pontine micturition reflex is controlled by inhibitory input from the medial frontal lobe, cingulate gyrus, hypothalamus, and periaqueductal gray. 4 , 5 A lesion above the pontine micturition center may cause uninhibited overactivity of the bladder with urinary incontinence. 6 A lesion at the brainstem interrupts the descending pathway from the pontine micturition center and may cause an emptying disorder of the bladder, engendering urinary retention.…”
mentioning
confidence: 99%